KARET ALAM SEBAGAI PENINGKAT MASA JALAN ASPAL - Enasty Pratiwi Wulandari (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2022)
Conventional asphalt comes from the cracking of petroleum which is a non-renewable natural resource whose reserves are continuously decreasing. This is due to the increasing use of asphalt for the construction of new roads, maintenance of existing roads and construction of expressways. To overcome the problem of reduced asphalt reserves, it is necessary to find alternative materials that can be renewed as asphalt mixture materials. The addition of alternative materials as an asphalt mixture must be able to improve the quality and service life of the road. Responding to existing problems, solutions are needed so that the use of conventional asphalt can be reduced without reducing road quality. Natural rubber is one of the materials that can be used as a mixture of conventional asphalt. The use of natural rubber as an asphalt mixture material from several research results at certain ratios can improve the quality of asphalt and the service life of the road. Indonesia as the second largest natural rubber producing country in the world after Thailand has the prospect of using natural rubber as an asphalt mixture. The use of natural rubber as an asphalt mixture material can provide positive benefits for the absorption of natural rubber while improving road quality and saving the use of conventional asphalt. In addition, the use of natural rubber as an asphalt mixture material can save the country's foreign exchange expenditure from asphalt imports. The policy of using natural rubber as an asphalt mixture material can provide a multiplier effect for the government, economic actors and the community.